EFFECT OF RED RICE, DESICCATED BY NON-SELECTIVE HERBICWES, ON IRRIGATED) RICE. I — PLANT ESTABLISHMENT AND DEVELOPMENT - NEVES, RODRIGO (1998)
Red rice is considered the most serious weed of rice crop in Rio Grande do Sul. Several techniques are usedto decrease the infestations in irrigated rice, among them, the use of minimum cultivation system. The objective of thisresearch was to evaluatc the effects of chemical management of red rice on plant characteristics of irrigated no-till rice, aswell as define the period in which such management can be performcd. A field trial was conducted during the growing seasonof 1996/97. Treatments in the field experiment consisted of rice desiccation periods (10, 6, and 2 days before, and 2 days afterrice sceding), non-selective herbicides (sulfosate at rates of 825 and 1650 g/ha, and paraquat at 400 g/ha), plus controtswithout herbicide application (with and without start nitrogen fertilizing), and systems of irrigated rice sowing (in presenceand in absence of red desiccated rice). The results showed that the presente of desiccated rice residues interfered negativelyon establishment, initial development, and final plant height of rice, especially when sowing occurred dose to herbicideapplication. Among the herbicides tested, sulfosate, especially the low rate, caused reductions for most of the parametersevaluated.